2018
DOI: 10.1080/14767058.2018.1517325
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter validation study of the WINROP algorithm as a method for detecting retinopathy of prematurity

Abstract: The WINROP screening algorithm in this study showed moderate sensitivity, so many ROP cases amenable to treatment were not detected. Other criteria should be added to the algorithm to increase the sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The point at which high‐risk alarms were triggered, the time between alarm triggers and treatment and the performance of WINROP were consistent with several studies . Unlike the initial validation papers , our study showed that WINROP was not perfect for screening threshold ROP and these findings agreed with a paper published in 2018 . Thus, with regard to the limits of gestational age and birth weight in the new but unpublished French guidelines on screening, we confirm that fundus examination remains necessary for infants born before 31 weeks of gestation or with birth weight of up to 1250 g. Nevertheless, the absence of WINROP triggering may allow waiving fundus examination for infants born at 31 weeks of gestation onwards or with birth weight of 1251 g or more.…”
Section: Discussionsupporting
confidence: 89%
“…The point at which high‐risk alarms were triggered, the time between alarm triggers and treatment and the performance of WINROP were consistent with several studies . Unlike the initial validation papers , our study showed that WINROP was not perfect for screening threshold ROP and these findings agreed with a paper published in 2018 . Thus, with regard to the limits of gestational age and birth weight in the new but unpublished French guidelines on screening, we confirm that fundus examination remains necessary for infants born before 31 weeks of gestation or with birth weight of up to 1250 g. Nevertheless, the absence of WINROP triggering may allow waiving fundus examination for infants born at 31 weeks of gestation onwards or with birth weight of 1251 g or more.…”
Section: Discussionsupporting
confidence: 89%
“…The full text was read for eligibility, of which 61 were included in the final analysis. The 61 studies (>37 000 infants) included WINROP (n = 36), 6 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 G-ROP (n = 9), 7 , 42 , 56 , 57 , 58 , 59 , 60 , 61 PINT ROP (n = 1), 8 CHOP ROP (n = 6), 9 , 30 , 55 , 62 , 63 , 64 ROPScore (n = 5), 10 , 30 , 55 , 65 , 66 and CO-ROP (n = 4). 11 , 67 , 68 , …”
Section: Resultsmentioning
confidence: 99%
“…The full text was read for eligibility, of which 61 were included in the final analysis. The 61 studies (>37 000 infants) included WINROP (n = 36), G-ROP (n = 9), PINT ROP (n = 1), CHOP ROP (n = 6), ROPScore (n = 5), and CO-ROP (n = 4) . Studies that used a different cutoff score for ROPScore were not included in the analysis …”
Section: Resultsmentioning
confidence: 99%